The Effect of Investment Risk and Return on Students Investment Decisions - Lathifah Suchie Nurhayathie; Vina Rosa Linda; Shofy Zahra Atika Putri; Trissya Nuraini; Thazsyah Nobillah (Universitas Dehasen Bengkulu, 2026)
This study aims to analyse the effect of investment risk and return on investment decisions among students at the University of Bengkulu. The growing interest of students in investment activities indicates that the younger generation is becoming more aware of the importance of financial planning for the future. However, as novice investors, students often face several challenges, such as limited knowledge and a tendency to be influenced by psychological, social, and informational factors, particularly those derived from social media, when making investment decisions. This research employs an explanatory quantitative approach. Data were collected via a questionnaire using a Likert scale, distributed to 54 respondents who are active students with investment experience. The sampling technique used was purposive sampling. Data analysis was conducted using multiple linear regression to examine the effects of investment risk and return, both partially and simultaneously, on students’ investment decisions. The results show that return has a significant influence on investment decisions, as students tend to prefer investment instruments that offer higher potential returns. Investment risk was also found to have a significant effect, although students’ understanding of risk varies. At the same time, both risk and return significantly influence investment decisions. The findings indicate that students are generally profit-oriented, whilst still considering risk in their decision-making process. This study is expected to enhance students’ financial literacy, enabling them to make more rational and balanced investment decisions.